Исследования устойчивости боковых пород в сложных горно-геологических условиях - Пугач, Иван Иванович; Подкопаев, Сергей Викторович; Иорданов, Игорь Вячеславович; Чепига, Дарья Анатольевна (НТУ "ХПИ", 2016)
В данной статье рассматриваются вопросы исследования устойчивости боковых пород горных выработок в условиях разработки крутых пластов. На основе выполненных исследований дается сравнение способов управления кровлей – полным обрушением и удержанием на кострах, а также закладкой выработанного пространства как средств, ограничивающих деформацию боковых пород. Представив породы кровли в виде балки и применив основные положения теории сопротивления материалов, выполнена оценка напряженно -деформируемого состояния пород и сделан вывод об эффективности применения закладки выработанного пространства.

The aim of the research is to study the stability of the wall rocks of mine workings in the conditions of development of steep seams. On the basis of the research compares the roof control methods - a complete collapse and holding at the chocks, as well as laying out space as a means of limiting the deformation of the wall rocks. Applying an optical method for studying the basic tenets of the theory of strength of materials and presenting rock roof in the form of beams, the estimate of the stress -strain state of the rocks and that the efficacy of stowing was concluded. It is proved that in comparative terms, geomechanical indicators application stowing much more efficient than traditional methods of control rock pressure. It was found that the filling mass prevents not only the displacement of rocks in the neighborhood of the mine workings, but also helps to eliminate the negative reasons in the virgin coal that can provoke the collapse of the wall rocks.
Investigation of the stability of wall rocks in difficult mining and geological conditions
Keywords: призабойное пространство; травматизм; управление кровлей; сдвижение горных пород; эпюры изгибающих моментов; rate of accidents; strata control; chock; bending moment diagram; face space